INTEGRATION OF THE RADEC MODEL IN ALTERNATIVE ENERGY TOPICS TO FOSTER CREATIVITY AS A TRAIT OF THE PANCASILA STUDENT PROFILE - Suhendi, Herni Yuniarti; Maulidah, Rifa'atul; Ariyanti, Vera (Journal of Teaching and Learning Physics, 2025)
This research was conducted to explore the effects of implementing the use of RADEC learning paradigm affects the Pancasila Student Profile's creative component, particularly in relation to alternative energy-related subjects. Using a matching-only posttest-only control group design, a quasi-experimental approach was used to select participants, with Class X.10 (36 students) serving as the control group and Class X.12 (36 students) as the experimental group. A posttest consisting of 10 essay questions that were all in line with the three creativity indicators listed in the Pancasila Student Profile was used to measure creativity. The research process included preliminary testing, expert validation, instrument trials, analysis of model implementation, the study also involved Hypothesis test through Test the significance level of α = 0.05. The results showed that the computed t-value (t = 8.4) was above the significance level critical t-value (t = 1.67), prompting acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (H0). These findings suggest that the RADEC model significantly enhances the creative dimension within the Pancasila Student Profile when applied to alternative energy material. The uniqueness of this study lies in its innovative application of the RADEC model in Physics instruction to foster student creativity and strengthen the creative competency within the Pancasila Student Profile framework.